سماجی ترقی میں نسوانی شراکت اور عہدِ نبوی ﷺکی خواتین کا کردار ؛ایک تجزیاتی مطالعہ: Feminine Contribution in Social Development and the Role of Women in the Prophet's Era: An Analytical Study - Nosheen, Sobia; Noreen , Farida (Al-Amīr Research Journal for Islamic Studies, 2023)
Being a complete code of life Islam allocates duties of everyone whether male or female. Both have allocated sphere of liabilities. But this is always a controversial issue that a female can participate in economic activities or not. This article provides the fact of women economical activities; they were costumer, investor, and administrator of market, Beautician, Doctors, Industrialist and agrarians. Although financial liability is allocated for the male member yet we came to know sometimes female were providing supports to their family. It means modern women can get guideline from the female of prophetic era. And they can best utilize their time and uplift their financial and moral threshold. Keywords: Role of Women, Social development, financial liability, Prophetic Era, Family Support.